Structural and Functional Characterization of Deceased Donor Stem Cells: A Viable Alternative to Living Donor Stem Cells. (25th November 2019) - Rao, Prakash N.; Deo, Dayanand D.; Marchioni, Misty A.; Taghizadeh, Rouzbeh R.; Cetrulo, Kyle; Sawczak, Sharyn; Myrick, Jacob
Abstract : Stem cells can be isolated from various human tissues including bone marrow (BM) and adipose tissue (AT). Our study outlines a process to isolate adult stem cells from deceased donors. We have shown that cell counts obtained from deceased donor BM were within established living donor parameters. Evaluation of demographic information exhibited a higher percentage of hematopoietic stem cells (HSC) in males versus females, as well as a higher percentage of HSC in the age bracket of 25 years and under. For the first time, we show that deceased donor femur BM grew cell colonies. Our introduction of new technology for nonenzymatic AT processing significantly increased cell recovery over the traditional enzymatic processing method. Cell counts from the deceased donor AT exceeded living donor parameters. Furthermore, our data illustrated that AT from female donors yielded a much higher number of total nucleated cells (TNC) than males. Together, our data demonstrates that our approach to isolate stem cells from deceased donors could be a routine practice to provide a viable alternative to living donor stem cells. This will offer increased accessibility for patients awaiting stem cell therapies.